Study of intracellular trafficking of yeast monocarboxylate transporter Jen1 from Saccharomyces cerevisiae - Talaia, Gabriel (2015)
The cell plasma membrane contains transmembrane proteins capable of recognizing and transporting a variety of compounds, such metabolites, nutrients and signaling molecules. Given the impermeability of the plasma membrane, the function, regulation and malfunction of these transporters is crucial for the cell. The intracellular traffic and turnover of transporters is highly regulated and well-studied in fungi and animal cells (Mukherjee et al., 2006; Lauwers et al., 2009; Steinbusch et al., 2011; Scheller, 2013; Liaunardy-Jopeace and Gay, 2014). Our group uses Jen1p, a lactate transporter of Saccharomyces. cerevisiae, as a model membrane cargo to study aspects of the mechanisms controlling the endocytic turnover of transporters in response to physiological signals and stress. Glucose triggers rapid endocytosis of Jen1p via its ubiquitylation by Rsp5p ubiquitin ligase (Paiva et al., 2002; Paiva et al., 2009), in a process that requires the arrestin-like adaptor Rod1 (Becuwe et al., 2012). Recently, it was described that when Rod1 is active, it is mostly localized at the trans-Golgi network (Becuwe and Leon, 2014). However, it remains largely unknown which Jen1 intracellular domains are targeted by Rod1p and Rsp5p, or how these trans-acting factors are recruited to Jen1p. Here, we performed domain swap experiments between Jen1p and other well-studied transporters, which respond to distinct endocytic signals, in order to further understand the specificity of interactions of membrane cargoes with factors of the ubiquitylation machinery. We will present the genetic strategy employed, as well as, data regarding the functional characterization of chimeric transporters.